2023
DOI: 10.1021/acs.jpcc.2c07928
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Ion and Chloride-Ion Transfer in Chiral and Racemic 3-Hydroxyquinuclidinium Perchlorate: Influence of Defects and a Mixed Plastic Crystal Matrix

Abstract: Organic ionic plastic crystals (OIPCs) are promising solid electrolytes. To observe the effect of defects and a mixed OIPC matrix on ionic conductivity, lithium-ion transfer and chloride-ion transfer in chiral and racemic (+/±)-3-hydroxyquinuclidinium perchlorate plastic crystals were studied. The pure chiral material and racemic mixture and their corresponding doped mixtures showed different thermal behaviors. Powder X-ray diffraction revealed that the cubic crystal structure appeared in both the high-tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…26,27 A recent study by Dong et al reported the interesting thermal and transport properties of pure chiral (+)-3hydroxyquinuclidinium perchlorate ((+)-[3-OH-QH]ClO 4 ) compared to racemic (±)-3-hydroxyquinuclidinium perchlorate ((±)-[3-OH-QH]ClO 4 ) and mixed systems. 28 Thermal phase behavior studies revealed that pure (+)-[3-OH-QH]-ClO 4 displayed one solid−solid transition, while racemic (±)-[3-OH-QH]ClO 4 showed no solid−solid transitions. Investigation of the transport properties of neat (+)-[3-OH-QH]ClO 4 showed increased ionic conductivity as the temperature is increased, with a sudden jump in values observed at the II−I phase transition (12 °C).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…26,27 A recent study by Dong et al reported the interesting thermal and transport properties of pure chiral (+)-3hydroxyquinuclidinium perchlorate ((+)-[3-OH-QH]ClO 4 ) compared to racemic (±)-3-hydroxyquinuclidinium perchlorate ((±)-[3-OH-QH]ClO 4 ) and mixed systems. 28 Thermal phase behavior studies revealed that pure (+)-[3-OH-QH]-ClO 4 displayed one solid−solid transition, while racemic (±)-[3-OH-QH]ClO 4 showed no solid−solid transitions. Investigation of the transport properties of neat (+)-[3-OH-QH]ClO 4 showed increased ionic conductivity as the temperature is increased, with a sudden jump in values observed at the II−I phase transition (12 °C).…”
Section: Introductionmentioning
confidence: 98%
“…Thermal phase behavior studies revealed that pure (+)-[3-OH-QH]­ClO 4 displayed one solid–solid transition, while racemic (±)-[3-OH-QH]­ClO 4 showed no solid–solid transitions. Investigation of the transport properties of neat (+)-[3-OH-QH]­ClO 4 showed increased ionic conductivity as the temperature is increased, with a sudden jump in values observed at the II–I phase transition (12 °C) . The sudden increase in ionic conductivity was attributed to the increase in onset of rotational motions/change in crystal structure as the OIPC sample is heated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations